2019
DOI: 10.1111/exd.13820
|View full text |Cite
|
Sign up to set email alerts
|

3‐O‐Laurylglyceryl ascorbate improves the development of sensitive skin through the reduction of oxidative stress

Abstract: Skin sensitivity is a serious problem for many people, and it can be induced by various factors such as UV irradiation, physical and mental stresses, air pollution, dry air and so on. Skin dryness triggered by UV and dry air is one of the most important causes inducing the development of sensitive skin, and it has been reported that oxidative stress contributes to skin dryness. In this study, we investigated whether treatment with 3‐O‐laurylglyceryl ascorbate (VC‐3LG), which is an amphipathic ascorbic acid der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Previously, PPAR‐α and PPAR‐γ, negative regulators of NF‐κB, are reported to be decreased in the inflamed lesions of psoriasis and AD 12,20 . On the contrary, DDH‐1 has been shown to exert an anti‐inflammatory effect by increasing the expression levels of PPAR‐α and PPAR‐γ 9–12 . Thus, we first confirmed the mRNA expression levels of PPAR‐α and PPAR‐γ in the skin lesions of AD‐like mice.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Previously, PPAR‐α and PPAR‐γ, negative regulators of NF‐κB, are reported to be decreased in the inflamed lesions of psoriasis and AD 12,20 . On the contrary, DDH‐1 has been shown to exert an anti‐inflammatory effect by increasing the expression levels of PPAR‐α and PPAR‐γ 9–12 . Thus, we first confirmed the mRNA expression levels of PPAR‐α and PPAR‐γ in the skin lesions of AD‐like mice.…”
Section: Resultssupporting
confidence: 67%
“…Accordingly, DDH-1, but not ascorbic acid, has been shown to promote the expression levels of peroxisome proliferator activated receptor (PPAR)α and PPARγ, nuclear factor-kappa B (NF-κB) negative regulators, in cultured keratinocytes, leading to reduced expression levels of TNFα, IL-1β and IL-6. [9][10][11][12] In addition, we have also found that DDH-1 shows an anti-inflammatory effect on a psoriasis mouse model induced by topical imiquimod treatment. 12 Thus, DDH-1 may also be useful to prevent and treat other inflammatory skin diseases including AD.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Recent examples of using skin explants include studies on penetration and metabolism of vitamin A derivatives 41 and the effect of cigarette smoke exposure on skin barrier permeability. 42 Where 3D skin equivalents and skin explants really shine is in their ability to model aspects of human skin disorders, including dry skin, 58 radiodermatitis 59 or hidradenitis suppurativa 60 Using an inhibitor to GSK3B with and without sunitinib, the authors showed that MAPK signalling and skin barrier gene expression changes can both be rescued, suggesting that GSK3B inhibitors may be a clinically relevant treatment to HFSR.…”
Section: Where Org Anot Ypi C S Kin Culture S " S Hine"mentioning
confidence: 99%
“…Where 3D skin equivalents and skin explants really shine is in their ability to model aspects of human skin disorders, including dry skin, 58 radiodermatitis 59 or hidradenitis suppurativa 60 to name but a few. In this issue of Experimental Dermatology , Yoshida et al .…”
Section: Where Organotypic Skin Cultures “Shine”mentioning
confidence: 99%